The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1093/oxfordjournals.aje.a009021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors in Children from the Belgian Province of Luxembourg: The Belgian Luxembourg Child Study

Abstract: The Province of Luxembourg is an area in Belgium with a high prevalence of risk factors for cardiovascular disease and non-insulin-dependent diabetes mellitus among adults. In the present study, children in the age groups 6-8, 8-10, and 10-12 years were selected at random from school classes (n = 1,028), with a participation rate of 70.3%. Anthropometric factors, blood pressure, and fasting blood glucose, plasma cholesterol, triglyceride, and insulin levels were measured in 1992. All anthropometric and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
2
42
1
7
Order By: Relevance
“…The expected prevalence of IRS2 if the criteria used to define it had clustered by chance alone would be 5.6%. Whatever mechanisms are underlying clustering of these metabolic risk factors, our data corroborate other reports [8][9][10][11][12] that they are operating at an early age. Trends in childhood IRS should be monitored because of their public health and clinical importance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The expected prevalence of IRS2 if the criteria used to define it had clustered by chance alone would be 5.6%. Whatever mechanisms are underlying clustering of these metabolic risk factors, our data corroborate other reports [8][9][10][11][12] that they are operating at an early age. Trends in childhood IRS should be monitored because of their public health and clinical importance.…”
Section: Discussionsupporting
confidence: 90%
“…6 IRS has been reported in both adults and children. [7][8][9][10][11][12] Although IRS in paediatric populations may have a profound impact on the future burden of disease, there are no data on its prevalence in representative samples of North American or European youth. Thus, the primary objectives of this study were (i) to examine the association between IR, and adiposity, blood pressure (BP), plasma glucose and lipids, (ii) to assess the clustering of metabolic risk factors, and (iii) to estimate the prevalence of IRS in a representative sample of youth in the province of Quebec, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Population studies of adults and children have demonstrated positive correlations between BP and both BMI and waisthip ratio. [33][34][35] The pattern of correlations in Table 3 indicates that the associations of BP with adiposity were underpinned by increased cardiac output, since correlations with total peripheral resistance were low or negative. A similar pattern has previously been described in comparisons of overweight and healthy weight adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Means of skinfold thicknesses in FLVS were similar to the 50th percentiles of the distributions for the same age range in healthy Dutch children, 27 and were slightly lower (0.5 ± 1 mm) than data in free-living children in Belgium. 28 The Netherlands and Belgium are two countries close to Fleurbaix and Laventie, which are in northern France.…”
Section: Discussionmentioning
confidence: 99%
“…No associations between STR or WHR and diet were observed, such as between WHR and cardiovascular risk factors in a former study. 28 This would indicate that, in prepubertal children, food intake has the same relationship with peripheral as with truncular fat.…”
Section: Discussionmentioning
confidence: 99%